The Basic Literature Of Usulu Al-Fiqkh And Furu Al-Fiqh Of The Khanafit School - KARIEV, Aiitmamat (Scientific Journal of Faculty of Theology, 2018)
The essence of the moslem way of life, it’s absolutly Holy Quran and Hadith. And they were analysed by different moslem people in a different way of ideologies. Khanafit school one of these different ideology schools. If we’ll some realistic assessment on the Khanafit school, of course we can find it’s superiority between others schools actually. We can to bring evidence to our thesis and that is it’s unique law systems, and it’s have been spreade in an all moslems countries, and it’s attract more supporters to itself, etc. and it’s others features. So every who holded in common khanafit school, he must have been some of knowledge about khanafit school. In this article we’ll research some factors what been effected in the khanafit schools infrastructure, and some reference books that writen in the furu al-fiqh and usulu al-fiqh of knowledge area.